Application of Short Interval Training Method Based on Low Maximum Aerobic Speed Capacity on Anaerobic Lactate Capacity Improvement - Fhonna, Putri; Sidik, Dikdik Zafar; Rosdiana, Fitri (Indonesian Journal of Sport Management, 2025)
This study aims to determine the effect of the Short Interval Training (SIT) method based on low Maximum Aerobic Speed (MAS) capacity on increasing anaerobic lactase capacity. This study used an Experimental method with a one-group pretest-posttest design. The population in this study was 24 athletes with a sample of 3 athletes. The instrument used was a 150-meter sprint test. The training program was carried out for 8 weeks with a total of 16 meetings. The results of the analysis showed a decrease in travel time from an average of 24.433 seconds to 23.527 seconds. This indicates that there is an effect between Short Interval Training (SIT) based on low Maximum Aerobic Speed on increasing Anaerobic Lactase with a significant value of 0.025, the value is smaller than 0.05. So it can be concluded that Short Interval Training (SIT) can increase Anaerobic Lactase capacity in Athletes who have low Maximum Aerobic Speed Effectively.